Plasma Prolidase Activity and Oxidative Stress in Patients with Parkinson’s Disease - Akhilesh Kumar Verma; Janak Raj; Vivek Sharma; Tej Bali Singh; Shalabh Srivastava; Ragini Srivastava (Parkinson's Disease)
Prolidase deficiency has been related to mental retardation and oxidative stress. The study aimed to observe plasma prolidase activity (PPA), total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) in patients with Parkinson’s disease (PD). 240 subjects with PD and 150 healthy volunteers were considered as cases and controls, respectively. PPA, TOS, TAS, and OSI were measured spectrophotometrically. PPA and TAS in cases were more significantly decreased than controls (P<0.01), while TOS and OSI were significantly increased (P<0.001). In cases, nonsignificant, positive correlation was observed between PPA and TOS and OSI while significant, negative correlation was observed between PPA and TAS (P=0.047). PPA in cases was nonsignificantly decreased with increased duration of PD (P=0.747) while TAS was significantly decreased (P<0.001) and TOS and OSI were significantly increased (P<0.001). It was observed that higher age groups had decreased PPA, and TAS and increased TOS and OSI compared to lower age groups in cases. In summary, patients with PD have decreased PPA and increased oxidative stress compared to healthy volunteers. PPA was associated with oxidative stress markers in patients with PD. Decreased PPA and TAS and increased TOS and OSI were associated with progression of disease and higher age.